Solving a long-standing nomenclatorial controversy: designation of a neotype for the southern sea lion Otaria flavescens (Shaw, 1800) - Lucero, Sergio; Rodríguez, Sara M.; Teta, Pablo; Cassini, Guillermo; D’elía, Guillermo (Zootaxa, 2019)
During almost two centuries, two available specific epithets have competed for the southern sea lions of the genus Otaria Péron, 1816 (Fig. 1), which is classically regarded as monotypic (but see below). The species distributes more or less continuously along the Atlantic coast from southern Brazil south to Cape Horn and along the Pacific from northern Peru to the west South American Pacific coast . While some researchers have argued that the correct name for this species is Phoca flavescens Shaw, 1800 (e.g., Cabrera, 1940, Rice, 1977; Rodriguez & Bastida, 1993; Teta et al., 2018), others have used P. byronia de Blainville, 1820 (e.g., Allen, 1905; Hamilton, 1934; King, 1978, Oliva, 1988; Berta & Churchill, 2012). This controversy originates from the fact that the diagnosis of the type of flavescens, the oldest epithet and as such the one that has priority, would not match the phenotypic features of the genus Otaria. This view, which favors the usage of byronia for populations of southern sea lions, was strongly defended by Oliva (1988:768), who argued that “…(1) the total length of the holotype [of flavescens]; (2) the size of the external ear; and (3) the color and length of the specimen’s fur do not correspond to any developmental stage of the species.” However, Rodríguez and Bastida (1993:378) discussed these same features reaching a very different conclusion, by indicating that “Shaw’s holotype, collected in the Strait of Magellan, could only have been a newborn pup of Otaria or Arctocephalus australis; its body size (circa 62 cm) could correspond to either species, but the uniform yellowish color is found exclusively in some molted pups of the Southern sea lion. Ear length, though not matching well with the described body length, lies within the recorded range of Otaria, but outside that for Arctocephalus australis.”